2011
DOI: 10.1039/c0cc04398b
|View full text |Cite
|
Sign up to set email alerts
|

Iron(iii) chloride-tandem catalysis for a one-pot regioselective protection of glycopyranosides

Abstract: Tandem catalysis by using iron(III) chloride hexahydrate leads to carbohydrate building blocks displaying an orthogonal protecting group pattern as illustrated by the regioselective protection of trehalose and maltose disaccharides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 38 publications
1
56
0
Order By: Relevance
“…However, mesenchymal stem cells have been found to significantly contribute in the wound healing process post-MI 14 . Previous studies have shown that myofibroblasts may originate from several sources, including expansion of resident fibroblasts, hematopoietic cells mobilized from bone marrow 12, 1517 , or from endothelial cells by the process of endothelial to mesenchymal transition (EndoMT) 18, 19 . Recent studies suggest that a subpopulation of heart-infiltrating BM-derived CD45 + cells expressing prominin 1 and other stem cell markers (such as cKit and Sca1), contribute to myoFB differentiation under the influence of pro-fibrotic factors TGFβ 15, 20, 21 .…”
Section: Introductionmentioning
confidence: 99%
“…However, mesenchymal stem cells have been found to significantly contribute in the wound healing process post-MI 14 . Previous studies have shown that myofibroblasts may originate from several sources, including expansion of resident fibroblasts, hematopoietic cells mobilized from bone marrow 12, 1517 , or from endothelial cells by the process of endothelial to mesenchymal transition (EndoMT) 18, 19 . Recent studies suggest that a subpopulation of heart-infiltrating BM-derived CD45 + cells expressing prominin 1 and other stem cell markers (such as cKit and Sca1), contribute to myoFB differentiation under the influence of pro-fibrotic factors TGFβ 15, 20, 21 .…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been reported that this protection reaction has been achieved through one‐step processes 728. However, these transformations require high temperature,7 extended reaction times,815 metal catalysts1627 or stoichiometric catalysis 28. Recently, the organocatalytic synthesis of 4,6‐benzylidene glycosides from aromatic aldehydes in one step under mild conditions was reported by Schmidt and co‐workers 29.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, developing environment-friendly, convenient, efficient and highly regioselective carbohydrate protection methods remains as one of the most prominent challenges [9]. Over the last several decades, many protection methods have been developed, including the use of reagents such as organotin [10][11][12], organoboron [13,14], organosilicon [15][16][17], metal salts [18][19][20][21][22][23], organobase [24][25][26], and enzymes [27][28][29][30]. Although these reagents each have advantages, they also possess troublesome shortcomings including inherent toxicity, high cost and the necessity to pre-protect secondary hydroxyl groups.…”
Section: Introductionmentioning
confidence: 99%